2010
DOI: 10.3892/or_00000746
|View full text |Cite
|
Sign up to set email alerts
|

The effect of siRNA-Egr-1 and camptothecin on growth and chemosensitivity of breast cancer cell lines

Abstract: Abstract.We have examined the effects of a siRNA targeting the Egr-1, alone or in combination with the breast cancer therapeutic camptothecin (Cpt), in suppressing breast cancer cell survival and anchorage-independent growth in the breast cancer cell lines SK-BR3 and MCF-7. In mammary and lung tumors, as well as most normal tissues, Egr-1 expression is low, suggesting a possible relation between the low levels of Egr-1 and the development of mammary neoplasias. However, analyses of the expression of Egr-1 in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
0
29
1
Order By: Relevance
“…In an effort to better understand the mechanisms responsible for these cellular responses, we measured the expression of Egr-1 protein and found that TGZ stimulates the expression of Egr-1 in a concentrationdependent manner. Egr-1 is a member of the immediate early gene response family and encodes a nuclear phosphoprotein involved in the regulation of cell growth and differentiation in response to signals such as mitogens, growth factors and stress stimuli (19)(20)(21). However, evidence suggests that Egr-1 binding sites are located within region -73 to -51 of the NAG-1 promoter, and the overexpression of Egr-1 results in increased NGA-1 expression.…”
Section: Discussionmentioning
confidence: 95%
“…In an effort to better understand the mechanisms responsible for these cellular responses, we measured the expression of Egr-1 protein and found that TGZ stimulates the expression of Egr-1 in a concentrationdependent manner. Egr-1 is a member of the immediate early gene response family and encodes a nuclear phosphoprotein involved in the regulation of cell growth and differentiation in response to signals such as mitogens, growth factors and stress stimuli (19)(20)(21). However, evidence suggests that Egr-1 binding sites are located within region -73 to -51 of the NAG-1 promoter, and the overexpression of Egr-1 results in increased NGA-1 expression.…”
Section: Discussionmentioning
confidence: 95%
“…At 14 days post treatment, plates were assessed for size and number of colonies (original magnification, x4). Colonies (in a representative field) are indicated (30,31).…”
Section: Methodsmentioning
confidence: 99%
“…Thermal cycle conditions were as follows: 42˚C for 30 min, 94˚C for 2 min, followed by 28 cycles of 94˚C 15 sec, 55˚C 30 sec, 72˚C 1 min, with a final extension at 72˚C for 10 min. RT-PCR products were visualized by ethidium bromide-stained agarose gels (30,32).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of siRNA involves post-transcriptional gene silencing via a process in which double stranded RNA (dsRNA) inhibits gene expression in a sequence-dependent manner through degradation of the corresponding mRNA. Its blocking action on gene expression has been successfully observed in rat and human cells cultured in vitro, and the knockdown of genes in cells has been achieved (12)(13)(14)(15). In addition, the development of retroviral constructs in which the polymerase-III H1-RNA gene promoter synthesizes siRNA-like transcripts, allows stable expression of siRNA, thus rendering this technology applicable as gene transfer (16,17).…”
Section: Introductionmentioning
confidence: 98%